Edukasi dan Pemeriksaan Gula Darah untuk Hidup Sehat Bebas Diabetes di Sungai Keledang - Bernadetha Bernadetha; Joko Sapto Pramono; Yona Palin (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Chronic diseases are non-communicable conditions that require a long time to heal and account for 70% of global deaths according to WHO (2024). One of the most common chronic diseases is diabetes mellitus, which requires medical treatment, self-management education, and continuous support to prevent complications. The International Diabetes Federation (2017) reported that the number of people with diabetes reached 427 million and is projected to increase to 629 million by 2045, with Indonesia ranking as the third-highest contributor globally. Poor diabetes management is often caused by patients’ noncompliance with healthy diet, exercise, and medication. The community still has limited understanding of the importance of blood glucose testing and proper care for family members with diabetes. Educational and blood glucose screening activities were carried out in Sungai Keledang Village, Samarinda Seberang, over three days in September 2025. The methods used included health education, interactive discussions, and blood glucose examinations. The results showed an increase in participants’ knowledge based on pretest and posttest scores on diabetes mellitus. The community was also actively involved in the screening and health education sessions.